A broad-spectrum orientation of supply chain network integration challenges: an empirical investigation using PLS path modelling. (1st November 2010) - Awad, Hussain A.H.; Nassar, Mohammad Othman
In order to achieve efficient supply chain integration for the processes or activities; the organisations should recognise and understand all the integration challenges of supply chain and the relations between those challenges. Our goal in this paper is to construct a novel statistical model that explores all challenges of supply chain integration and the relations between them. In this paper, we validated our proposed model through an empirical investigation using partial least square (PLS) path modelling.